A Modified Suture Suspension Arthroplasty Technique for the Treatment of Basal Joint Arthritis: Short- to Intermediate-Term Outcomes. (November 2021) - Mirza, Ather; Mirza, Justin B.; Klingbeil, Laura; Pavlik, Joseph F.; Muratori, Jonathan; Thomas, Terence
Background: To present a retrospective study on the outcomes of a modified version of suture suspension arthroplasty with trapeziectomy on patients with thumb basal joint arthritis and to evaluate the relationship between the degree of subsidence and functional outcome.Methods: We performed a chart review on 67 patients (75 thumbs) who were surgically treated for thumb carpometacarpal osteoarthritis with trapeziectomy and suture suspension arthroplasty from May 2010 to May 2016. Outcome measures included Disabilities of the Arm, Shoulder and Hand (DASH), grip strength, lateral/precision pinch strength, range of motion, and return to work/resumption of usual activities. Radiographic images were used to measure first metacarpal subsidence into the trapezial space.Results: Clinical outcomes were satisfactory, showing an initial postoperative DASH score of 45.94, which decreased to 27.93 at 6 months postoperatively and to 19.69 at 1 year postoperatively. Radiographic images revealed a mean first metacarpal subsidence of 39% compared with the preoperative images. Grip and pinch strengths showed steady improvement from initial postoperative to final follow-up visits, resulting in 90% recovery of gross grasp, 77% recovery of lateral pinch, and 79% recovery of precision pinch compared with the contralateral side.Conclusions: Our study has found that suture suspension arthroplasty with trapeziectomy is an effective treatment for thumb basal joint arthritis. Suture suspension arthroplasty allows for short immobilization time, avoids tendon sacrifice, avoids anchor use, and leaves a cosmetically appealing scar. Furthermore, a relationship of any significance between postoperative first metacarpal subsidence and functional outcomes does not appear.